International neurocognitive normative study: neurocognitive comparison data in diverse resource-limited settings: AIDS Clinical Trials Group A5271 - K. Robertson (2018)
© 2016, Journal of NeuroVirology, Inc. Infrastructure for conducting neurological research in resource-limited settings (RLS) is limited. The lack of neurological and neuropsychological (NP) assessment and normative data needed for clinical interpretation impedes research and clinical care. Here, we report on ACTG 5271, which provided neurological training of clinical site personnel and collected neurocognitive normative comparison data in diverse settings. At ten sites in seven RLS countries, we provided training for NP assessments. We collected normative comparison data on HIV− participants from Brazil (n = 240), India (n = 480), Malawi (n = 481), Peru (n = 239), South Africa (480), Thailand (n = 240), and Zimbabwe (n = 240). Participants had a negative HIV test within 30 days before standardized NP exams were administered at baseline and 770 at 6 months. Participants were enrolled in eight strata, gender (female and male), education (<10 and ≥10 years), and age (<35 and ≥35 years). Of 2400 enrolled, 770 completed the 6-month follow-up. As expected, significant between-country differences were evident in all the neurocognitive test scores (p < 0.0001). There was variation between the age, gender, and education strata on the neurocognitive tests. Age and education were important variables for all tests; older participants had poorer performance, and those with higher education had better performance. Women had better performance on verbal learning/memory and speed of processing tests, while men performed better on motor tests. This study provides the necessary neurocognitive normative data needed to build infrastructure for future neurological and neurocognitive studies in diverse RLS. These normative data are a much-needed resource for both clinicians and researchers.